1999
DOI: 10.1016/s0305-0491(99)00017-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemically detected ontogeny of prolactin and growth hormone cells in the African catfish Clarias gariepinus

Abstract: The chronological appearance of selected endocrine cells in the pituitary of African catfish Clarias gariepinus (Burchell, 1822) was studied morphologically, histologically and immunohistochemically by using antisera raised against catfish growth hormone (cgGH) and recombinant tilapia prolactin I (tPRL). cgGH-and tPRL-like immunoreactive cells were visible from day 1 post fertilisation (hatching) throughout the juvenile and the adult stage. From 1 to 90 days after hatching, the larval pituitary is oval in shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The defined localisation of cells immunoreactive for PRL in the RPD and for GH around the neurohypophyseal processes in the PPD as found in the present study has been observed for various teleosts (Yan and Thomas 1991;Power 1992;García-Hernández et al 1996;Weltzien et al 2003b;Volckaert et al 1999;Laiz-Carrión et al 2003), including tilapia (Nishioka et al 1993;Nagahama et al 1981;Mousa and Mousa 1999a,b).…”
Section: Discussionsupporting
confidence: 85%
“…The defined localisation of cells immunoreactive for PRL in the RPD and for GH around the neurohypophyseal processes in the PPD as found in the present study has been observed for various teleosts (Yan and Thomas 1991;Power 1992;García-Hernández et al 1996;Weltzien et al 2003b;Volckaert et al 1999;Laiz-Carrión et al 2003), including tilapia (Nishioka et al 1993;Nagahama et al 1981;Mousa and Mousa 1999a,b).…”
Section: Discussionsupporting
confidence: 85%
“…Several cytochemical investigations focused on the identification and localization of ADH cells types in teleost species, including representative species of the following orders: Cyprinodontiformes (Batten, ), Osteoglossiformes (Borella et al, ), Perciformes (García‐Ayala et al, ; Villaplana et al, ; Pandolfi et al, ); Clupeiformes (Laiz‐Carrión et al, ), Salmoniformes (Naito et al, ), Siluriformes (Volckaert et al, ), Cypriniformes (Chapman et al, ), Osmeriformes (Saga et al, ), Pleuronectiformes (Einarsdóttir et al, ), and Atheriniformes (Vissio et al, ). Among the reophilic Neotropical species, only S. hilarii (Honji et al, ), S. brasiliensis (Jesus et al, ) and Piaractus mesopotamicus (Borella et al, ), all Characiformes, were previously analyzed, adding for the first time to the list the tropical catfish S. parahybae in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The early and almost simultaneous appearance of ir‐GH, ir‐PRL and ir‐SL cells suggests a common origin from a primordial stem cell, as hypothesized in the sea bream Sparus aurata (L. 1758) (Perciformes) (Villaplana et al ., ). In freshwater and brackish water teleosts, the ir‐GH cells appeared before hatching (Naito et al ., ; Saga et al ., , ) or around or immediately after hatching, for example at 1 dah in the African catfish Clarias gariepinus (Burchell 1822) (Siluriformes) (Volckaert et al ., ), at 1·5 dah in S. brasiliensis (de Jesus et al ., ) and at 2 dah in D. rerio (Herzog et al ., ). In marine teleosts the ir‐GH cells were detected at hatching or upon yolk absorption (Cambré et al ., ; Power & Canario, ; Tanaka et al ., ; Laiz‐Carrión et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Only cells showing an entire nucleus on the slide were measured. The ratio of cell area to nucleus area was used as a measure of cell activity (Volckaert et al, 1999).…”
Section: Analysis Of Pituitary Cell Area and Nucleus Areamentioning
confidence: 99%